“Waiting for a Wife”: Transnational Marriages and the Social Dimensions of Refugee “Integration” - Brunner, Lisa Ruth; Hyndman, Jennifer; Mountz, Alison (Refuge: Canada's Journal on Refugees, 2014)
This paper addresses the gap in research on the social dimensions of refugee resettlement. This is accomplished by examining refugee belonging and definitions of “integration”through a case study of Acehnese refugees resettled in Vancouver, British Columbia, between 2004 and 2006. We analyze findings based on a survey and in-depth interviews conducted five years after resettlement. Our findings suggest that recently resettled groups like the Acehnese, who are “new and few,” face specif c integration challenges. Importantly,the lengthy timelines to enact sponsorship of a spouse and/or family reunification from Aceh unwittingly inhibit the social integration of the sponsors waiting in Canada.